2012
DOI: 10.1080/00140139.2012.665497
|View full text |Cite
|
Sign up to set email alerts
|

Acute cold exposure and cognitive function: evidence for sustained impairment

Abstract: Several industries experience periods of cold exposure and rewarming throughout the workday but mental performance under these conditions is unknown. A better understanding of cognition during the rewarming phase after cold exposure may help reduce accidents and improve performance. Ten young men (wearing~0.1 clo) underwent 3 consecutive mornings trials where they were exposed to cold air (10°C) and then subsequently re-warmed (25°C air). A computerized test battery was administered during each stage of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 27 publications
5
79
2
1
Order By: Relevance
“…In a US study, subjects were exposed to cold conditions (10ºC) and then to 25ºC [368]. The authors concluded that cognitive function is reduced during the cold exposure and that such reduction persisted for one hour during the rewarmed period [368]. In China, another study involving two groups of subjects (one exposed to temperature variations and the other exposed to 26°C) concluded that a warm discomfort environment had a negative effect on performance.…”
Section: Thermal Comfort and Productivitymentioning
confidence: 97%
See 1 more Smart Citation
“…In a US study, subjects were exposed to cold conditions (10ºC) and then to 25ºC [368]. The authors concluded that cognitive function is reduced during the cold exposure and that such reduction persisted for one hour during the rewarmed period [368]. In China, another study involving two groups of subjects (one exposed to temperature variations and the other exposed to 26°C) concluded that a warm discomfort environment had a negative effect on performance.…”
Section: Thermal Comfort and Productivitymentioning
confidence: 97%
“…Another study in a climate chamber in a non-steady thermal environment in Denmark (users could only change their clothes) found no difference in productivity amongst the analyzed thermal conditions (19.0-26.8ºC) [367]. In a US study, subjects were exposed to cold conditions (10ºC) and then to 25ºC [368]. The authors concluded that cognitive function is reduced during the cold exposure and that such reduction persisted for one hour during the rewarmed period [368].…”
Section: Thermal Comfort and Productivitymentioning
confidence: 98%
“…Pilcher et al (2002) performed meta-analysis and demonstrated that under cold conditions (~10 °C) reasoning, learning and memory tasks were impaired. Exposure to acute cold stress impairs the performance of short-term or working memory (Thomas et al, 1989;Duncko et al, 2009) and attention (Teichner, 1958;Muller et al, 2012). Baddeley et al (1975) reported a significant decrement in memory recall but not in recognition; however, other authors have reported a significant decrement in recognition but not in recall (Ellis et al, 1985).…”
mentioning
confidence: 99%
“…Moreover, some investigators used a model in dogs and compared ice-water immersion (1 to 3 °C), coldwater immersion (10 to 11 °C), and tap-water immersion (15 to 16 °C) and found no significant differences among the 3 immersions (Magazanik et al, 1980). Most of investigations analyzing cold stress responses to cognitive performance were limited by exposure time (Mäkinen et al, 2006;Lieberman et al, 2009;Muller et al, 2012;Seo et al, 2013), but in a recent study Brazaitis et al (2014) induced cold stress by body immersion in cold water and examined the physiological responses in two groups of subjects: those who exhibited a fast decrease in rectal temperature (T re ) (fast cooling, FC) and those who exhibited a slow decrease in T re (slow cooling, SC). Accordingly, we assume that cold exposure, limited by time in earlier studies, might induce different responses on T re and subject's cognitive function could be affected differently.…”
mentioning
confidence: 99%
See 1 more Smart Citation